I’RADH SUAMI DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Afroo, Fakhriyah Annisa (UIN Fatmawati Sukarno Bengkulu, 2018)
Husband’s i’radh In Islamic And Positive Law Perspective, i’radh is the husband who turns away, husband’s i’radh is the beginning of the cause of the emergence of nusyuz. In the positive law of Law No. 1 of 1974 concerning Marriage and compilation of Islamic Law does not mention the problem of the husband’s husband explicitly. However, according to the author, a husband can be considered as an iadrad if inside him contains the elements of the husband who violate taklik talak. differences and similarities in the views of husbands in the perspective of Islamic law and positive law, among others. In Islamic law, it is explicitly mentioned that i’radh in positive law does not explicitly mention i’radh or nusyuz husband. In Islamic law and positive law both use the path of peace, but when the peace that is done is unsuccessful, the wife can file a divorce. So that this husband could be the cause of the wife’s divorce case against the husband when he was already in the behavior, while when he was still within the boundary he could not be the reason for the divorce